Was steckt hinter dem Campingboom? Ergebnisse empirischer Feldforschung zur Analyse von deutschen Campingtourist:innen - Kristina Sommer (IU Internationale Hochschule, 2022)
– This discussion paper addresses the demand for camping tourism by means of a literature review and an exploratory empirical study based on it. There was little data available specifically on motives of campers. Previous studies, such as those conducted by the Society for Consumer Research (Gesellschaft für Konsumforschung), the ADAC or the Erwin Hymer Group, have shown that the main motives for camping vacations are independence, flexibility and proximity to nature. This discussion paper supports these findings with regard to tourist campers and supplements them with the motive of family-friendliness. For wild campers, on the other hand, freedom in addition to tranquility and closeness to nature play a role in terms of motives. Tourist campers mainly inform themselves about camping vacations on the internet and social media as well as by talking to friends and family members. In terms of route planning, most prefer a campground as a specific destination. When campers book their campsite in advance, they do so online or by emailing the campsite directly. Wild campers plan their wild camping stay primarily online. Travel agents do not play a role in camping vacations. Most tourist campers use a caravan or motorhome as their accommodation for their camping vacation. Few stay in a tent. Wild campers mainly use the motorhome. The most popular destination in terms of the last longer camping vacation for almost half of the respondents was Germany, ahead of Italy.
Keywords: 650; Camping; Touristikcamping; Wildcamping; Dauercamping; Caravaning; Naturtourismus